An evaluation of cytokine and cellular immune responses to heterologous prime-boost vaccination with influenza A/H7N7-A/H7N9 inactivated vaccine - Hana M El Sahly; George Makedonas; David Corry; Robert L Atmar; Abbie Bellamy; Kaitlyn Cross; Wendy A Keitel (Taylor & Francis Group, 2020)
The immunologic mechanisms underlying the improved serologic responses to heterologous prime-boost avian influenza vaccination are unclear. An exploratory analysis of the immune responses following 1 dose of influenza A/H7N9 inactivated vaccine in subjects who received an influenza A/H7N7 inactivated vaccine (N = 17) 8 years earlier or who were influenza A/H7-naïve (10) was performed. Plasma IL-6 and IL-21 concentrations by ELISA, the frequency of A/H7N7-specific memory B cells and antibody secreting cells by ELISpot, the frequency of circulating T follicular helper cells and the frequency of T cells expressing IL-6 and IL-21 by flow cytometry were assessed at baseline (D1), and 8 days (D9) and 28 days (D29) after vaccination. We assessed the correlation between these measurements and the D29 serologic responses to the boost vaccine. Plasma IL-6 concentration on D9 significantly correlated with the H7N7 and H7N9 hemagglutination inhibition (HAI) antibody levels (P = .03 and 0.02 respectively); and the percentage of T cells expressing IL-21 on D9 significantly correlated with H7N9 HAI antibody seroconversion (P < .001). Significant associations with other immunologic markers were not detected. We detected an association between plasma IL-6 and intracellular IL-21 and serologic responses to heterologous prime-boost avian influenza vaccination. A clarification of the role of these and additional immunologic markers requires larger clinical trials.